Alcohol consumption, dependence and foraging. (2nd November 2017) - Phillips, James G.; Hughes, Barry; Ogeil, Rowan P.
ABSTRACT: Background: Smartphone technology enables treatment providers to deliver targeted outpatient support "on site" in "real time, " but this will require a better understanding of peer networks and substance users' acquisition of drugs. Objectives: This study sought to understand contextual factors associated with risky levels of alcohol consumption. Methods: A total of 280 participants answered an online survey, completed the AUDIT and indicated their numbers of regular drinking partners, and the number of times and places alcohol was normally consumed. Results: Hazardous drinkers had a greater number of drinking partners and drank alcohol at a greater number of times and locations. Alcohol dependence was associated with alcohol use in more times and places, but was not linked to the numbers of drinking partners. Models drawn from foraging literature were used to describe the data. Conclusions/Importance: Patterns of alcohol foraging could be described by power laws, and such power laws could be used to compare foraging for a range of substances. A consideration of foraging behavior may inform location-aware services targeting risky substance use.